The effects of strikes in the South African gold mining industry on shareholder value - Seedat, Aayesha (My University, 2013)
The recent spate of strikes in the mining sector in South Africa has created a perceived nervousness amongst shareholders. Within the mining sector in South Africa, gold mining is of significance historically and economically. This study aims to assess the impact of strikes on shareholder value in the gold mining industry during the period beginning January 2007 and December 2012, and uses the popular event study methodology developed by Ball and Brown (1968). The effect of the announcement and duration of the strike on the share price was tested. Significant negative cumulative abnormal returns were observed during the announcement of the strike. The impact of the announcement of protected strikes compared to unprotected strikes on the share price was compared. Although both types of strikes had a negative impact on shareholder value, an unprotected strike had less of an impact on shareholder value compared to a protected strike. This observation is of particular significance given the recent increase in unprotected strikes. Strikes with a duration of 15 days or longer resulted in smaller negative cumulative abnormal returns as opposed to strikes which lasted for less than 15 days.
Thesis (M.Com. (Accounting))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2012.
Keywords: Strikes; Gold mines; South Africa; Shareholder value